The Dysfunctional Scenario of the Major Components Responsible for Myocardial Calcium Balance in Heart Failure Induced by Aortic Stenosis - da Silva, Vitor Loureiro [UNESP] (2022)
Background: Maladaptive cardiac remodelling is characterized by diastolic and systolic dysfunction, culminating in heart failure. In this context, the dysfunctional scenario of cardiac calcium (Ca2+) handling has been poorly studied. An experimental model of aortic stenosis has been extensively used to improve knowledge about the key mechanisms of cardiac pathologic remodelling. Objective: To understand the dysfunctional process of the major components responsible for Ca2+ balance and its influence on cardiac function in heart failure induced by aortic stenosis. Methods: Male 21-day-old Wistar rats were distributed into two groups: control (sham; n= 28) and aortic stenosis (AoS; n= 18). Cardiac function was analysed by echocardiogram, isolated papillary muscle, and isolated cardiomyocytes. In the papillary muscle assay, SERCA2a and L-type Ca2+ channel activity was evaluated. The isolated cardiomyocyte assay evaluated Ca2+ handling. Ca2+ handling protein expression was analysed by western blot. Statistical significance was set at p <0.05. Results: Papillary muscles and cardiomyocytes from AoS hearts displayed mechanical malfunction. AoS rats presented a slower time to the Ca2+ peak, reduced Ca2+ myofilament sensitivity, impaired sarcoplasmic reticulum Ca2+ influx and reuptake ability, and SERCA2a and L-type calcium channel (LTCC) dysfunction. Moreover, AoS animals presented increased expression of SERCA2a, LTCCs, and the Na+/Ca2+ exchanger. Conclusion: Systolic and diastolic heart failure due to supravalvular aortic stenosis was paralleled by impairment of cellular Ca2+ influx and inhibition of sarcoplasmic reticulum Ca2+ reuptake due to LTCC and SERCA2a dysfunction, as well as changes in Ca2+ handling and expression of the major proteins responsible for cellular Ca2+ homeostasis.